Preventive Approach: Anti-Bullying Awareness to Build a Friendly, Safe, and Supportive School Environment for Children’s Dreams at SDN Tuwung 2, Kahayan Tengah District, Pulang Pisau Regency - Haliza Fatimah; Rino Hartanto; Yuniarti Musdalifah; Meidy Nelwan; Mega Novi Septiani; Annisha Hafiizh; Aprilia Andreini; Khalisah; Ahmad (PT Polstac Repositori Riset, 2026)
Background: In an effort to create a safe and friendly school environment, a socialization program entitled “Turn Off Bullying, Turn on Dreams” was implemented at SDN Tuwung 2. This activity aimed to increase students’ understanding of bullying, including its forms and impacts, as well as to instill values of empathy and the courage to report bullying behavior. Contribution: The main problems addressed in this program included the persistence of bullying behaviors that are still socially tolerated among students, limited understanding of what constitutes bullying, and a lack of confidence to report such incidents. Method: This initiative is expected to reduce the incidence of bullying and to enhance students’ sense of safety and comfort at school. The implementation of these preventive measures is essential to support children’s social and emotional development. Results: The results of the activities show an collaboration among the school, teachers, and university students in delivering the program is expected to create an environment that not only promotes academic learning but also fosters character building. Conclusion: With a shared commitment to combating bullying, SDN Tuwung 2 is expected to become a place that supports the growth and dreams of every child.